Hospitais com características organizacionais diferenciadas: aplicação do QFD nos serviços de fisioterapia - Cortez Neto, Angelo (2003)
This work aimed to characterize, to measure and to develop the quality of the physiotherapeutic service in three different hospitals. To reach the objectives quality indicators they were used (IDs) and the quality function deployment. The obtained results, through those two tools, they suggest to invest in the students' training; to aim the motivation and interpersonal relationship; to provide the safety in the practical theoretical knowledge and to accomplish a multidisciplinary with the medical team. These relationships of the results of the tools facilitate the scientific administration of a physiotherapy service, the "QFD" turns possible the characterization of the quality and because of this it selects the technical or administrative actions based on the customer's opinion for the improvement of the service, and the "IDs", evaluate the characteristics of the quality of their customers' service, however, those tools should be applied periodically for the continuous improvement of the quality of the service.